Word usage variations in Arabic newspapers: a corpus investigation - Zainur Rijal Abdul Razak (Penerbit UKM, 2014)
The Modern Standard Arabic (MSA) is practiced in all Arab countries especially in official communication; written and spoken to unite Arab countries in certain aspects. However, a standardization of the Arabic language, particularly in the word usage is needed between Arabic countries. Seven Arabic newspapers from different countries which contain a corpus of around 87,000 words from World Affairs section are used to highlight the differences of word usage. This research is based on a theory (Kilgarriff, 2001) which states that the analysis of the consistency of word usage in corpora or sub-corpora can reveal the lexical choices. This study focuses on the discussion of several types of variations of nouns and verbs usage. The software Wordsmith 5.0 was utilized to analyze the corpus by extracting all words into frequency list and concordance. The results show that the Arabic newspapers had a great contribution in creating word usage variations, specifically in terms of spelling, loan word acceptance, verbs transitivity to particle, phrase combinations and plural formations. In some cases, the influence of foreign language such as English plays an important role in creating variation of Arabic language usage. The results of this study is hoped to increase the awareness of newspaper readers around the world regarding the significant variations in Arabic language usage and its transformations over the years.